Ocurrence of Excilorana mayana (Isopoda: Cirolanidae) in a sandy mid- littoral beach of Punta Paitilla, Pacific coast of Panamá - Dominici Arosemena, Arturo; Garcés, Humberto (Boletín del Centro de Investigaciones Biológicas)
Quantitative sediment samples collected on the Pacific coast of Panama, at Punta Paitilla during the 1991-1992 rainy and dry seasons in the sandy mid-littoral zone were characterized by a dominant population of Excirolana mayana. The E. mayana population was characterízed by the following mean values: abundance, 169 org./m2; total length, 3.7 mm; and wet weight, 410 mg. The occurrence of a significant population of E. mayana on the eastern pacific entrance of the Panama Canal is reported for the first time. This dominant population of E. mayana may serve for trans-oceanic comparative studies. The protection of this population in areas of continuous urban development is needed.